Funds of Knowledge and Global Competence in Urban Middle Schools - Jalene Tamerat (Middle Grades Review, 2020)
Global competence—a necessary attribute in an increasingly interconnected world—describes having the knowledge, skills, and dispositions to act creatively and collaboratively on important global issues. In urban settings comprised of racial, ethnic, and/or linguistic-minority students, especially, a logical but seemingly underutilized facilitator of global competence would be instruction that draws from students’ funds of knowledge—the home-based practices central to a household’s functioning and well-being. In this study, 30 Boston-area teachers were interviewed using a semi-structured protocol to draw out their understandings of students’ funds of knowledge and their awareness of how these funds of knowledge might be used to further the development of global competence. Data produced in this study were analyzed through a multi-phase thematic coding process. A conceptual framework built upon existing definitions of global competence and funds of knowledge was developed and used as a guide for viewing and understanding the produced data. The two major findings of this study were that: (1) middle school teachers, while seemingly able and willing to talk about global competence and funds of knowledge in relation to their students, did not seem to synthesize (or speak about their synthesis of) these concepts in practice, and, (2) in teacher interviews, potential global competence-supporting funds of knowledge were most often recognized in immigrant and/or economically privileged White middle school students. The potential global competence-supporting funds of knowledge possessed by non-immigrant, BIPOC, and presumably, low-income students were not routinely recognized or accessed.
Keywords: Global competence; funds of knowledge; third space; middle school; urban education